Surface Integrity Analysis when Milling Ultrafine-grained Steels - Rodrigues, Alessandro Roger; Balancin, Oscar; Gallego, Juno [UNESP]; Fazolo de Assis, Cleiton Lazaro; Matsumoto, Hidekasu [UNESP]; de Oliveira, Fernando Brandao [UNESP]; da Silva Moreira, Suzana Regina [UNESP]; da Silva Neto, Otavio Villar (Universidade Federal de São Carlos (UFSCar), Dept Engenharia Materials, 2012)
This paper quantifies the effects of milling conditions on surface integrity of ultrafine-grained steels. Cutting speed, feed rate and depth of cut were related to microhardness and microstructure of the workpiece beneath machined surface. Low-carbon alloyed steel with 10.8 mu m (as-received) and 1.7 mu m (ultrafine) grain sizes were end milled using the down-milling and dry condition in a CNC machining center. The results show ultrafine-grained workpiece preserves its surface integrity against cutting parameters more than the as-received material. Cutting speed increases the microhardness while depth of cut deepens the hardened layer of the as-received material. Also, deformations of microstructure following feed rate direction were observed in workpiece subsurface.
Keywords: milling; surface integrity; microstructure; microhardness; ultrafine-grained steel